2019
DOI: 10.3390/app10010025
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of Cellulose-Based Activated Carbon Fiber for Acetaldehyde Adsorption at Low Concentration

Abstract: The toxic nature of acetaldehyde renders its removal from a wide range of materials highly desirable. Removal of low-concentration acetaldehyde (a group 1 carcinogenic volatile organic compound) using an adsorbent of cellulose-based activated carbon fiber modified by amine functional group (A@CACF-H) is proposed, using 2 ppm of acetaldehyde balanced with N2/O2 (79/21% v/v) observed under continuous flow, with a total flow rate of 100 mL/min over 50 mg of A@CACF-H. The effective removal of the targeted acetalde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Therefore, AC 4 , which is an impregnated AC, can be considered a promising adsorbent for the adsorption of acetaldehyde from the air. These results are supported by those of a previous study in which the adsorption capacity of impregnated AC using various impregnants was explored based on their steric structure and acidity for acetaldehyde adsorption [29]. Therefore, the highest adsorption of acetaldehyde by AC might be achieved because of lesser benzene ring presence in the impregnated amine that hinders the condensation of acetaldehyde.…”
Section: Acetaldehyde Adsorption By the Selected Carbon-based Adsorbentssupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, AC 4 , which is an impregnated AC, can be considered a promising adsorbent for the adsorption of acetaldehyde from the air. These results are supported by those of a previous study in which the adsorption capacity of impregnated AC using various impregnants was explored based on their steric structure and acidity for acetaldehyde adsorption [29]. Therefore, the highest adsorption of acetaldehyde by AC might be achieved because of lesser benzene ring presence in the impregnated amine that hinders the condensation of acetaldehyde.…”
Section: Acetaldehyde Adsorption By the Selected Carbon-based Adsorbentssupporting
confidence: 85%
“…The adsorption capacity of AC for acetaldehyde removal has been reported to not be promising, as discussed in the literature [24, 4 28]. It was reported that the acetaldehyde adsorption capacity of impregnants AC is affected by the steric structure and acidity [29]. A recent study showed that cellulose-based AC fibers (CACFs) can be used as a potential adsorbent for the adsorption of acetaldehyde from the air [30].…”
Section: Introductionmentioning
confidence: 99%
“…These aminated ACs showed a greater improvement in the adsorption performance in various adsorption processes. The mechanism of FA is described in our previous report [63]. Considering urea as an amine source, the carbonyl group of FA adsorbs onto the active sites (micro-walls) of AC (HCHO( g ) → HCHO( ad.…”
Section: Approaches To Chemical Modifications Of the Ac Surfacementioning
confidence: 91%
“…In addition, no change in the structure of BAC is observed, as there is almost no change in the -CH2 groups. Ryu et al [34] reported that the amine functional groups on activated carbon lead to a higher CH 3 CHO adsorption efficiency, and thus, the amine groups should increase CH 3 CHO adsorption.…”
Section: Chemical Characterizationmentioning
confidence: 99%